Administrative reforms in India - Singh, Mahendra Prasad (2012)
The broad thrusts of administrative reforms in India have aimed at three basic goats: improving the efficiency of administration internally and in relation to service delivery to the citizens; maintaining the thin line of demarcation between political neutrality of administration and party politics; and curbing corruption. The major problem that administrative reforms in India face is the abysmal record of lack of implementation of the series of reports of the various commissions. Still much is left to be done to initiative simple administrative and institutional reforms to improve delivery of pubic services, reduce scope for corruption and increase ministerial accountability. The article highlights the need r eforms. - Reproduced.
Keywords: Administrative reforms - India; Administrative reforms